Framework for Intelligent-Electricity Billing and Consumption Information System (IEBCIS) - Esiefarienrhe, Bukohwo Michael; Maine, Itumeleng Michael (Universitas Bina Darma, 2024)
The increasing demand for energy, coupled with the depletion of natural resources and environmental concerns, necessitates the adoption of sustainable energy practices. The use of electricity sustainability principles and smart meters data integration into energy systems plays a crucial role aiding electricity users make informed decisions about their energy consumption, driving sustainable energy practices and improving environmental stewardship. Despite efforts at electricity innovations, challenges persist in improving existing electricity frameworks, particularly in enhancing security and privacy measures, optimizing energy efficiency, improving user engagement and awareness, and addressing sustainability, scalability, interoperability, reliability and mounting environmental concerns and global warming issues. The integration of the principles of electricity sustainability and smart meter data into the development of a framework for Intelligent-Electricity Billing and Consumption Information System (IEBCIS) is crucial and an optimized approach to tackle these issues moving forward. Therefore, this paper presents IEBCIS framework that incorporated key aspects of electricity sustainability, interoperability, scalability, usability, reliability, security and privacy in the design of its framework. The Action Design Research (ADR) methodology using the pragmatism research philosophy was used to develop software prototypes to elucidate requirements for testing the framework. The result from the prototype showed significant potential to transform electricity billing and consumption practices by empowering users to make informed decisions about their energy usage, driving sustainable energy practices and improving environmental stewardship. Using the prototype, electricity consumers were able to access their smart data, query their electricity bills, simulate various electricity reduction best practices and view their total energy proposed savings in rands (South Africa currency). Ultimately, the IEBCIS framework achieved its aim of contributing to a more efficient and sustainable energy ecosystem, aligning with the global imperative for sustainable energy practices.